Volume 1: Pipelines and Facilities Integrity 2016
DOI: 10.1115/ipc2016-64511
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of Buried Gas Pipeline Subjected to an Adjacent Pipe Rupture Event

Abstract: This paper discusses the integrity of 30” OD pipeline subjected to burst of 24” pipeline located 24’ away. Study discusses the detailed finite element analyses (FEA) of pipeline subjected to the stress waves emanating from the rupture event. Dynamic response of a 30” gas pipe buried approximately 6.5’ deep was studied using ABAQUS, to determine how it may have been affected by the rupture of an adjacent 24” gas pipe. The pressure at the 24” OD pipe was dropped from flow pressure to zero psi in a very short int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cozzani et al [50] suggested that underground gas pipeline ruptures can form ground craters due to the forceful release of gas, with surrounding soil acting as a protective barrier for adjacent pipelines outside the crater but rendering those within vulnerable to pressure and heat [51]. Additionally, researchers utilized ABAQUS ® software to assess potential impacts on pipelines from adjacent ruptures [52].…”
Section: Research Significancementioning
confidence: 99%
“…Cozzani et al [50] suggested that underground gas pipeline ruptures can form ground craters due to the forceful release of gas, with surrounding soil acting as a protective barrier for adjacent pipelines outside the crater but rendering those within vulnerable to pressure and heat [51]. Additionally, researchers utilized ABAQUS ® software to assess potential impacts on pipelines from adjacent ruptures [52].…”
Section: Research Significancementioning
confidence: 99%
“…Published research has focused on studying the crater formation mechanism and its dimensions but in underground explosions of TNT (Ambrosini et al, 2002;Ambrosini and Luccioni, 2006;Luccioni et al, 2009;Xin-zhe et al, 2013;Krishna et al, 2016). However, only a few studies have specifically focused on the formation of craters by the explosive rupture of buried pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…There are some approaches such as the Gasunie, Battelle, Advantica or the NEN 3651 models (Leis M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT et al, 2002;Acton et al, 2010;NSI, 2012) that were developed based on experimental results which depend on soil properties from the pipeline location. There are other approaches that use TNT explosion models based on a set of experiments or FEM (Finite Elements Modeling) (Ambrosini et al, 2002;Ambrosini & Luccioni, 2006;Krishna et al, 2016). Finally, there is an approach called the Accident-based model recently proposed by Silva et al (2016) which implements a polynomial regression on 17 underground accidents.…”
Section: Introductionmentioning
confidence: 99%